Cotton's fluctuating fortunes in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
In the course of the last 30 years cotton-growing has expanded steadily in the savanna lands of francophone Africa. On the other hand, during the same period, production in the English-speaking countries has declined sharply. Now, however, all the...